2022
DOI: 10.1039/d2nj00210h
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of time-dependent density functionals for the electronic excitation energies of organic dyes used in DSSCs

Abstract: The absorption spectra modeled as the vertical excitation energies of 13 dye sensitizers used in dye-sensitized solar cells (DSSCs) are benchmarked by means of time-dependent (TD)-DFT, using 36 functionals from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 130 publications
0
15
0
Order By: Relevance
“…Another point to consider is that the long alkyl chains at position 8 that are also typical in dye sensitizers are modeled with a simple methyl group in all dyes explored in the present work. This approximation will have no effect on the electronic structure and spectra of the BODIPY highly conjugated systems, and is a valid modeling strategy frequently used to reduce the computational cost of calculations [60, 61, 140–142]. Finally, we will only be interested in the effect of methyl groups in the present study, and we will not study the effect of the nature of the substituent on the spectra, since it was previously found by Mukherjee that electronic structure of BODIPY compound is only affected by the position and not by the nature of the substituent [46].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Another point to consider is that the long alkyl chains at position 8 that are also typical in dye sensitizers are modeled with a simple methyl group in all dyes explored in the present work. This approximation will have no effect on the electronic structure and spectra of the BODIPY highly conjugated systems, and is a valid modeling strategy frequently used to reduce the computational cost of calculations [60, 61, 140–142]. Finally, we will only be interested in the effect of methyl groups in the present study, and we will not study the effect of the nature of the substituent on the spectra, since it was previously found by Mukherjee that electronic structure of BODIPY compound is only affected by the position and not by the nature of the substituent [46].…”
Section: Resultsmentioning
confidence: 99%
“…However, many previous studies demonstrated the validity of using the vertical approximation for BODIPY compounds [63, 77]. Therefore, all our ES results are performed according to the vertical excitation model [60, 61, 63, 73, 77, 144]. Furthermore, in an experimental photovoltaic solar cell device, the dye sensitizers together with the I/I3 electrolyte redox couple are usually dissolved in an organic solvent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations